2022
DOI: 10.3390/cancers14174317
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Stakeholders’ Perception of the Impact of COVID-19 on Clinical Care and Decision-Making

Abstract: Background: Pandemics are related to changes in clinical management. Factors that are associated with individual perceptions of related risks and decision-making processes focused on prevention and vaccination, but perceptions of other healthcare consequences are less investigated. Different perceptions of patients, nurses, and physicians on consequences regarding clinical management, decisional criteria, and burden were compared. Study Design: Cross-sectional OnCoVID questionnaire studies. Methods: Data that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…For example, it was difficult to keep all members of large, multidisciplinary teams up-to-date with aerosol-generating procedures in theatre. This is consistent with findings in other studies where it has been reported that constantly changing protocols created ambiguity in how care was expected to be delivered (Chemali et al, 2020), and studies which highlighted challenges associated with incorporating multiple, new items of information into making decisions (Haier et al, 2022a). It is recognized that specialized the COVID-19 knowledge and experience was evolving during the first wave of the pandemic (Chemali et al, 2020;Lavoie, Bourque, Côté, et al, 2022), and thus it is important that clinicians recognize that decisions could only be based on the information available at the time (Lavoie, Bourque, Côté, et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…For example, it was difficult to keep all members of large, multidisciplinary teams up-to-date with aerosol-generating procedures in theatre. This is consistent with findings in other studies where it has been reported that constantly changing protocols created ambiguity in how care was expected to be delivered (Chemali et al, 2020), and studies which highlighted challenges associated with incorporating multiple, new items of information into making decisions (Haier et al, 2022a). It is recognized that specialized the COVID-19 knowledge and experience was evolving during the first wave of the pandemic (Chemali et al, 2020;Lavoie, Bourque, Côté, et al, 2022), and thus it is important that clinicians recognize that decisions could only be based on the information available at the time (Lavoie, Bourque, Côté, et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…Clinician decisions are typically complex, dynamic, and considerate of patient outcomes (Schuttner et al, 2022 ). The Australian government declared a national emergency response to the COVID‐19 pandemic in March 2020 and this decision‐making complexity was exacerbated during the first wave of the COVID‐19 pandemic as rapidly emerging evidence and experience meant that pandemic modelling, policies, and clinical protocols were constantly evolving (Chemali et al, 2020 ; de Caestecker & von Wissmann, 2021 ; Haier et al, 2022a ). Clinicians were required to make decisions locally to balance patient care with their safety, determine which patients to treat based on resource availability, and accept less comprehensive care for some patient cohorts (Iserson, 2020 ; Lavoie et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%